Intracerebral Transplants of GMP-Grade Human Umbilical Cord-Derived Mesenchymal Stromal Cells Effectively Treat Subacute-Phase Ischemic Stroke in a Rodent Model - Noh, Jeong-Eun; Oh, Seung-Hun; Park, In-Hyun; Song, Jihwan (Frontiers in Cellular Neuroscience, 2020)
In the subacute and chronic phases of stroke, there are currently no effective treatment for functional recovery. Human umbilical cord-derived mesenchymal stromal cells (hUC-MSCs) are one of the candidate cell sources for the treatment of subacute phase stroke. Therapeutic benefits gained from cell-based therapy largely depend on the migratory capacity, extent of cell engraftment in the target tissues and their paracrine activity. Timing and delivery route of stem cells can also influence the outcome of cell therapy. However, it remains to be elucidated how the different routes of hUC-MSC delivery affect cell replacement and cell-to-cell paracrine effect for functional recovery in the subacute phase of stroke. In this study, we compared therapeutic effects of different delivery routes of Good Manufacturing Practice (GMP)-grade hUC-MSCs in a rodent model of subacute-phase stroke. The 1ⅹ106 hUC-MSCs were injected intravenously (IV) or transplanted intracerebrally (IC) at 1 week after middle cerebral artery occlusion (MCAo) in rats, and the transplanted animals were examined up to 7 weeks after transplantation using various behavioral tests and immunohistochemical analyses. Most IC-transplanted cells survived for short period of time (i.e., less than 4 weeks after transplantation) and disappeared gradually afterwards. The IV-injected cells were not detected in the brain at the same time points (i.e., 3 days, 4 weeks and 7 weeks after injection). Although IC-transplanted cells didn’t survive for long periods of time, they were effective in improving behavioral deficits, reducing infarct volume and glial scar formation, and increasing the number of proliferating neuroblasts in the subventricular zone and cerebral vessel formation in the ischemic penumbra region. However, IV injection was not effective in improving behavioral function and histological parameters at 7 weeks after injection. Taken together, our results suggest that IC transplantation is a preferable route of delivery of hUC-MSCs than IV injection in the subacute-phase stroke.